8‐Hydroquinolatolithium as a Highly Effective Solution‐Processable Cathode Interfacial Material in Inverted Perovskite Solar Cells with an Efficiency Over 19%. Issue 9 (6th June 2018) - Ye, Senyun; Rao, Haixia; Zhang, Dongyang; Bian, Mengying; Zhao, Zifeng; Gu, Feidan; Zhao, Ziran; Chen, Yinlin; Zhou, Huiqiong; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : The solution‐processed 8‐hydroquinolatolithium (Liq) has first been demonstrated as a highly effective cathode interfacial layer (CIL) in inverted perovskite solar cells (PSCs). Compared with the control device without a CIL, the Liq‐based device possesses a faster charge transport rate, a lower surface work function of Ag electrode, a larger built‐in potential, and a higher charge recombination resistance, probably due to the formed interface dipole between [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PCBM) and Ag induced by Liq, which eventually results in a great improvement of device performance. After optimization, the Liq‐based PSC has achieved a power conversion efficiency higher than 19%. These results will assuredly expand the present limited range of available solution‐processable cathode interfacial materials for low‐cost high‐performance PSCs. Abstract : Solution‐processed 8‐hydroquinolatolithium (Liq) has first been demonstrated as a highly effective cathode interfacial layer between PCBM and Ag cathode to fabricate perovskite solar cells (PSCs) with a full solution‐processed method. After optimization, an efficiency as high as 19.1% has been achieved, which is beneficial for improving the cost performance of PSCs and promoting their practical applications.